2017
DOI: 10.5194/aab-60-33-2017
|View full text |Cite
|
Sign up to set email alerts
|

Influences of breed, sex and age on seasonal changes in haematological variables of tropical goat kids

Abstract: Abstract. The influences of breed, sex and age on seasonal changes in haematological variables of kids (1-4 months old) belonging to Red Sokoto (n = 60) and Sahel (n = 60) goats were studied at the peaks of the cold-dry, hot-dry and rainy seasons in a West Africa Guinea savanna climate. The results showed that, during the hot-dry season, Sahel goat kids had significantly higher (P < 0.05) packed cell volume (PCV) and red blood cell (RBC) count but lower (P < 0.05) mean corpuscular volume (MCV), mean corpuscula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 36 publications
5
8
1
1
Order By: Relevance
“…Sheep sent for grazing exhibited lower Hb, PCV and RBC contents. These results are in line with those reported elsewhere ( Habibu et al., 2017b ; Banerjee et al., 2014 ; Singh et al., 2016 ). Sejian et al.…”
Section: Discussionsupporting
confidence: 94%
“…Sheep sent for grazing exhibited lower Hb, PCV and RBC contents. These results are in line with those reported elsewhere ( Habibu et al., 2017b ; Banerjee et al., 2014 ; Singh et al., 2016 ). Sejian et al.…”
Section: Discussionsupporting
confidence: 94%
“…The sheep reared in extensive and semi-intensive farming systems showed higher EOF due to the higher THI. Similar reports were reported elsewhere [ 21 , 23 ]. The stress caused by increased body temperature may enhance the production of free radicals, thereby causing lipid peroxidation.…”
Section: Discussionsupporting
confidence: 92%
“…An increase in BHB in goat blood determined with increased age was within the physiological range, since Doré et al (2015) reported a hypoketonemia definition based on BHB concentrations from ≥ 0.4 to ≥ 0.9 mmol L −1 . According to Herdt (2000) BHB is more likely a reflection of nutritional status and less constrained physiologically.…”
Section: Discussionmentioning
confidence: 99%